2014
DOI: 10.4081/aiua.2014.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Urinary and sexual functions after surgical treatment of penile fracture concomitant with complete urethral disruption

Abstract: On the long term follow-up, most of the patients maintained their normal erectile and voiding functions with no harmful long-term complications. We advocate immediate surgical intervention and reconstruction of both corpora cavernous and urethra as a first line treatment for those patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 31 publications
3
25
0
Order By: Relevance
“…El-Assmy et al used uroflowmetry in patients with urethral injury after surgical treatment of PF and found abnormal urinary flow due to urethral stenosis in only one case ( 20 , 21 ). Raheem et al observed similar results and only one of ten patients had abnormal flow ( 4 ). RGU is recommended when abnormalities are found in the IPSS questionnaire or uroflowmetry to identify possible urethral stricture or other complications.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…El-Assmy et al used uroflowmetry in patients with urethral injury after surgical treatment of PF and found abnormal urinary flow due to urethral stenosis in only one case ( 20 , 21 ). Raheem et al observed similar results and only one of ten patients had abnormal flow ( 4 ). RGU is recommended when abnormalities are found in the IPSS questionnaire or uroflowmetry to identify possible urethral stricture or other complications.…”
Section: Discussionmentioning
confidence: 65%
“…Some authors recommend suprapubic cystostomy in cases of complete circumferential rupture. They believe that it is safer to place a suprapubic catheter and and recommend keeping it closed for at least 3 days after urethral catheter removal to ensure adequate and normal voiding before its removal ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8] Sequelae of urethral injuries in the setting of penile fracture can include urethral stricture or pseudodiverticula. 9,10 Evaluation of the urethra can be performed with a variety of techniques including cystoscopy or urethrography. Magnetic resonance imaging, which is occasionally used to confirm penile fractures, can also identify urethral injuries.…”
Section: Resultsmentioning
confidence: 99%
“…Recent literature advocates surgical treatment for penile fracture and/or urethral injury as soon as possible as this appears related to fewer complications and better outcomes. 3,15…”
Section: Discussionmentioning
confidence: 99%